New developments in health insurance: A step towards preventive health care - Trifković Nada (Association of Nurses Technicians and Midwives, 2019)
According to the proposal of the Law on Health Insurance, which entered the parliamentary procedure, patients who did not respond to the proposed preventive examinations and procedures will pay 35% of the treatment. Preventive health care is a compulsory and primary part of health care, which involves several levels of the organization and realization: • Raising awareness of the population on the importance and need for preventive health care • Mandatory by law and legal regulation of preventive health care • Organization and coordination of health institutions in the implementation and monitoring of preventive care • Qualified staff for all forms of preventive health care, which implies the implementation of these topics and contents in nursing education programs or the development of a special preventive health care program. • Development of a Program for monitoring preventive health care that would be connected to the Internet in all health centers and institutions (unique code of patients) CONCLUSION: In order to introduce and monitor a high quality preventive health care, besides raising awareness of the importance of the same, it is necessary to provide adequate conditions and to train staff which will implement preventive health care. The progress towards preventive health care as a mandatory part of health care, based on the example of developed countries, is a priority task of the Ministry of Health and Ministry of Education, Science and Technological Development and cooperation between these two ministries in terms of organization (Ministry of Health) and education (Ministry of Education, Technological Development) is of great importance for the implementation of preventive health care in our healthcare system.